PERAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA DI SEKOLAH DASAR - Dhina Cahya Rohim; Septina Rahmawati (Universitas Negeri Surabaya, 2020)
ABTRACTThe purpose of this study was to determine the role of literacy activities, obstacles and efforts made by the school in increasing reading interest in elementary school students. This research is a qualitative research. The research subjects were the principal, teachers and fourth grade students of Kutoharjo 02 Elementary School. The technique of collecting data was through interviews, observation and documentation. Based on the results of the research it can be seen that 1) literacy activities play a role in increasing students' reading interest, 2) obstacles in carrying out literacy activities in schools include the lack of infrastructure, the methods applied are less varied and the low discipline of students in the process of habituating literacy activities, and 3 ) efforts made by the school to overcome these obstacles are by providing socialization about literacy activities, adding facilities and holding competition activities as a forum for students to actively participate.Keywords: elementary school students, literacy, reading interest. ABSTRAKTujuan penelitian ni adalah untuk mengetahui peran kegiatan literasi, hambatan dan usaha yang dilakukan pihak sekolah dalam meningkatkan minat baca siswa sekolah dasar. Penelitian ini merupakan penelitian kualitatif. Subjek penelitian adalah kepala sekolah, guru dan siswa kelas 4 Sekolah Dasar Negeri Kutoharjo 02. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Berdasarkan hasil peneltian dapat dilihat bahwa 1) kegiatan literasi berperan dalam meningkatkan minat membaca siswa, 2) hambatan dalam melaksanakan kegiatan literasi di sekolah diantaranya adalah kurangnya saranaa prasarana, metode yang diterapkan kurang variatif serta rendahnya kedisiplinan siswa dalam proses pembiasaan kegiatan literasi, dan 3) usaha yang dilakukan pihak sekolah dalam mengatasi hambatan tersebut adalah dengan memberikan sosialisasi mengenai kegiatan literasi, menambah sarana serta mengadakan kegiatan perlombaan sebagai sarana partisipasi aktif siswa.Kata Kunci: literasi, minat membaca, siswa sekolah dasar